Transformasi dan Dinamika Hukum Acara Perdata di Indonesia: Integrasi Asas, Sistem Pembuktian, dan Digitalisasi Peradilan - Fredy Ied Fitriadi; Aldhitama Ramadhan; Fasub Hanal; Jimmi MP Aritonang (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study examines the foundational framework and evolving dynamics of Indonesian civil procedural law (Hukum Acara Perdata) amid its transformation from colonial legal heritage toward a modern, digitalized justice system. Using normative-doctrinal legal research methodology combined with empirical court statistics from 2022–2024, the study analyzes four dimensions: (1) core procedural principles rooted in the HIR and RBg; (2) the mandatory mediation framework under PERMA No. 1 of 2016; (3) the evolution of evidence law toward electronic evidence under the amended UU ITE (Law No. 1 of 2024); and (4) mechanisms of judicial decisions and legal remedies. Findings show that e-court implementation has dramatically increased efficiency minutasi productivity rose from 64.35% (2022) to 96.50% (2024)—while 594,816 users registered through e-court by 2023. The study concludes that Indonesia’s civil procedural law is actively adapting to technological disruption, though structural challenges such as digital inequality, electronic evidence authentication gaps, and regulatory harmonization remain unresolved.